Active Vibration Control of Functionally Graded Carbon Nanotube Reinforced Composite Plate with Coupled Electromechanical Actuation - Yu, X. L.; Zhang, X. H.; Wang, J. F. (Frontiers in Materials, 2022)
Piezoelectric materials possess the electromechanical coupling characteristic, which are used to realize structural vibration control. This paper investigates the active control of free and forced vibration for piezoelectric integrated functionally graded carbon nanotube reinforced composite (FG-CNTRC) plate using finite element method (FEM). Based on the first order shear deformation theory (FSDT), the governing equations of motion of piezoelectric integrated FG-CNTRC plate are derived by Hamilton principle. The convergence and accuracy of numerical method is verified through the results of natural frequencies. The influences of CNT volume fraction, CNT distribution type, dimension ratio and boundary condition on the natural frequencies are investigated for piezoelectric integrated FG-CNTRC plate. A constant gain velocity feedback algorithm is used to achieve the dynamic response control of piezoelectric integrated FG-CNTRC plate. In addition, the effects of dynamic load, feedback control gain and boundary condition on the dynamic response of plate are studied. Numerical results indicate that active control is promising for the practical applications in civil and mechanical engineering.